Faktor Yang Berhubungan dengan Partisipasi Peserta BPJS Kesehatan dalam Kegiatan Skrining di UPT Puskesmas Rappang - Rosmayanti; Pratiwi Ramlan; Zulkarnain Sulaeman; Mardhatillah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2026)
Participation of BPJS Health participants in screening activities remains low, particularly at UPT Puskesmas Rappang, which only reached 12.7% of 21,615 participants in 2025. This low coverage indicates the presence of factors influencing community participation in early disease detection programs. This study aimed to analyze the relationship between knowledge, attitudes, and health worker support with participation in screening activities. This study used a quantitative approach with a cross-sectional design. Sampling was conducted using accidental sampling. Data were collected through questionnaires, observation, and documentation, and analyzed using chi-square tests. The results showed that attitude (p=0.01) and health worker support (p=0.01) had significant relationships with participation, while knowledge (p=0.40) was not significantly related. This indicates that knowledge alone is insufficient to drive behavior without supportive attitudes and external encouragement. In conclusion, participation is more influenced by attitudes and health worker support rather than knowledge. Therefore, behavior-based health education and strengthening the role of health workers are essential to improve community participation in screening programs.